Social innovation as a collaborative concept - Ziegler, Rafael (Innovation: The European Journal of Social Science Research, 2017)
The rise of social innovation expresses a discontent with innovation as we know it, and its ability to deliver just and sustainable outcomes. Yet, social innovation is also notoriously vague as a concept, thereby putting into doubt whether the concept offers any real improvements or alternatives. This paper issues an invitation to think about social innovation as a collaborative concept. The conceptual framework shows collaboration, rather than contestation, to offer a space for the working together of different perspectives and actors. The collaborative concept frame welcomes and seeks to explain a diversity of uses. Singling out key features of social innovation as a collaborative concept, it seeks to contribute to an emerging practice that makes different contributions part of a progressive conversation about social innovation, the evaluative ideas associated with it and the evidence from policies and projects. Identifying transformative, taxonomical and transitional–sceptical uses of social innovation, the paper highlights the importance of analysing the evaluative aspects of the multisectoral reconfigurations associated with social innovation so as to keep track of its role for justice and sustainability.
Keywords: Collaboration; Innovation sociale; Éthique